2018
DOI: 10.1093/ofid/ofy210.1668
|View full text |Cite
|
Sign up to set email alerts
|

2012. FilmArray® Measurement of Host Response Signatures RapidLy Discriminates Viral, Bacterial, and Non-infectious Etiologies of Illness

Abstract: BackgroundThe inability to reliably discriminate bacterial, viral, and non-infectious illness has led to an epidemic of antibiotic overuse and rising rates of antimicrobial resistance. Host gene expression provides a powerful approach to distinguish infection etiologies and guide appropriate therapy. However, existing platforms for transcriptomic analysis are not amenable for clinical application. The FilmArray platform is a sample-to-answer multiplex RT-PCR system that automates transcriptomic analysis includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Clinic-ready platforms capable of operationalising PCR-based signatures of the size tested herein already exist, some of which are approved with point-of-care functionality, offering a proximal pathway to clinical application of these findings. 46 Thus, analysis of the evolution of gene expression-based biomarkers over time shows promise for driving development of diagnostics for early detection of viral exposure and infection that could prove useful for guiding administration of early effective therapy, quarantine decisions, and other clinical and public health interventions in the setting of endemic and pandemic infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…Clinic-ready platforms capable of operationalising PCR-based signatures of the size tested herein already exist, some of which are approved with point-of-care functionality, offering a proximal pathway to clinical application of these findings. 46 Thus, analysis of the evolution of gene expression-based biomarkers over time shows promise for driving development of diagnostics for early detection of viral exposure and infection that could prove useful for guiding administration of early effective therapy, quarantine decisions, and other clinical and public health interventions in the setting of endemic and pandemic infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we have shown that a single transcript (IFI27) detects SARS-CoV-2 infection with high accuracy. If translated to a near-patient diagnostic test (34, 35) , this transcript could have significant clinical utility by facilitating early case detection.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our findings suggest that a single transcript ( IFI27 ) discriminates between individuals with mild early SARS-CoV-2 infection and uninfected healthy individuals with high accuracy. If translated to a near-patient diagnostic test, 46 , 47 this transcript could have substantial clinical utility by facilitating early case detection.…”
Section: Discussionmentioning
confidence: 99%